2017
DOI: 10.1080/13621718.2016.1194735
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life assessment of weld joints manufactured by GMAW and CW-GMAW processes

Abstract: The fatigue strength of weld joints manufactured using gas metal arc welding and cold wire GMAW (CW-GMAW) was evaluated under stress-controlled cyclic loading. The material used in this study was class ASTM 131 grade A steel, joined using ER70S wire filler metal. The addition of cold wire led to a decrease in the amount of intergranular ferrite and an increase in hardness in the heataffected zone. The assessment of fatigue life was performed by using the Weibull distribution and the results revealed that with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…Subsequent research [10] studied the effect of the CW-GMAW on process-induced residual stresses, concluding that welds manufactured by CW-GMAW have lower levels of residual stresses. This decrease in residual stresses might explain the improvement in fatigue life reported in [11].…”
Section: Introductionmentioning
confidence: 69%
“…Subsequent research [10] studied the effect of the CW-GMAW on process-induced residual stresses, concluding that welds manufactured by CW-GMAW have lower levels of residual stresses. This decrease in residual stresses might explain the improvement in fatigue life reported in [11].…”
Section: Introductionmentioning
confidence: 69%
“…Ribeiro et al [13] carried out a predicting weld bead geometry study for the CW-GMAW process, where the deposition rate increases by cold wire addition. CGHAZ reduction was also expected due to a lower heat input and faster cooling rate associated with cold wire increment [12]. Further, deposition rate values in the experimental parameters are 100% higher than the industry.…”
Section: Geometric and Cghaz Analysismentioning
confidence: 82%
“…However, the high temperatures of the weld process incorporated residual stresses with a decrease in their ballistic performance. Marques et al [12] observed a ferrite reduction in the CGHAZ, confirming a modification in the microstructure by the addition of cold wire and the faster cooling rate due to less heat input associated with the CW process. In addition, an increase in the microhardness is associated with this rate increment, observed in Fig.…”
Section: Geometric and Cghaz Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, it is not possible to guarantee a high quality weld with regard to a sufficient corrosion resistance as well as high strength of the welded joint. In addition, the mechanical properties are influenced by the high cooling rates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%